Invite Only Dinner with Bernard Witkin at Basque Hotel - Watkins, Howard::::::::: (1986)
Bernard Witkin standing and talking; on left facing: ?, Justice Hollis Best, Judge Robert Mardikian, backside: Jim Barstow, Judge Leonard Meyers, Peter Morris; head table: Judge James V. Paige, Judge Frank Creede, Jr., Bernie Witkin, Judge Robert Coyle, James Gregory; seated close: Judge Harold Thompson, Justice Charles Hamlin, Judge Gene Gomes; Judge Milo Popovich in bottom right corner.